Ant Group Effects on the Insecticide and Dye Flow Among Atta sexdens rubropilosa (Hymenoptera: Formicidae) Workers - Barbieri, Rafael F. [UNESP] (2009)
Social behavior has conferred many advantages upon insects. Allogrooming and self-grooming, frequently observed among leaf-cutting ants, help to prevent colony contamination by microorganisms and aid in the process of recognizing nest-mates, given the evidence that the grouping effect acts to modulate these behavioral parameters. For Ellis reason, the contamination dynamic was evaluated in workers of Atta sexdens rubropilosa by particles adhering externally to the tegument of their bodies, with and without the presence of insecticide added to dye in different groupings. The results demonstrate that although the dye had dispersed rapidly among workers in all groupings, it was eliminated efficaciously only in groups that utilized the dye without insecticide. When compared by the chi-square test (X(005)(2); 3) at 60 minutes only, the group containing the most individuals (128) presented significant values and at 120 minutes only the smallest group (16 individuals) did not present significant values, indicating that the greater the number of individuals the more rapidly it would be dispersed among nest-mates, thus elevating the importance of utilizing active ingredients with a delayed action in the control of leaf-cutting, ants, to avoid detection of insecticide by the colony and enable its propagation to all or most of the colony before triggering, the defense mechanisms of the colony.